Significant reduction in spin pumping efficiency in a platinum/yttrium iron garnet bilayer at low temperature. (5th April 2016) - Shigematsu, Ei; Ando, Yuichiro; Ohshima, Ryo; Dushenko, Sergey; Higuchi, Yukio; Shinjo, Teruya; Jürgen von Bardeleben, Hans; Shiraishi, Masashi
Abstract: The temperature evolution of a direct-current electromotive force (EMF) generated by spin pumping and the inverse-spin Hall effect in a platinum (Pt)/yttrium iron garnet (YIG) bilayer was investigated down to 80 K. The magnitude of the EMF decreased significantly with decreasing temperature and disappeared at approximately 80 K. 40-nm-thick YIG films fabricated by a metal organic decomposition method exhibited single-peak ferrimagnetic resonance (FMR) spectra without any spin wave resonance, which allowed us to precisely analyze the FMR spectra. We determined that the temperature evolution of the Gilbert damping constant is the dominant factor in the temperature dependence of the EMF. The comparison of the FMR linewidth between the X- and Q-bands revealed that an increase in Gilbert damping constant at low temperatures is not due to the enhancement of the spin pumping efficiency but due to an additional spin relaxation in the YIG film itself, which reduces the precession angle of the magnetization under the FMR conditions.